The efficacy of combined nutrition education and nutritional supplementation on nutritional status of prospective brides to prevent stunting in newborns - Pramoni, Ni Gusti Ayu K. Dewi; Tanziha, Ikeu; Briawan, Dodik; Khomsan, Ali (International Journal Of Community Medicine And Public Health, 2022)
Background: Optimal growth and development of children is an indicator of the quality of human resources. Stunting is a condition of linear growth retardation which is the result of a long-term lack of nutrients. The stunting problem prevention program is prioritized in the first 1000 days of and the bride and groom who will later become pregnant and give birth to offspring. The purpose of this study was to determine the effect of a combination of nutritional education and nutritional supplementation on changes in the nutritional status of the prospective bride and groom to prevent stunting in newborns. Methods: The design was quasi-experimental with a pre-post intervention in Sumbawa Regency, West Nusa Tenggara in June 2020 to October 2021. Sample size: 126 of prospective brides aged 20-30 years who were divided into 3 groups. Data analysis used Paired t-test, Wilcoxon, ANOVA and Kruskal Wallis. Results: Mean BMI after intervention: 22.08±3.12 kg/m2. The intervention reduced the underweight category from 31 (24.6%) to 19 (15.1%). The average weight gain of pregnant women after the intervention was 63.08±7.02 kg. Statistical test there was a difference between groups (p = 0.000). The effect of intervention on infant anthropometry was 13 (11.21%) body length <48 cm and 11 (9.48%) LBW and 10 (8.62%) abnormal head circumference. Conclusions: The intervention can change the parameters of the nutritional status of the subject and there is a relationship between weight gain during pregnancy and infant anthropometry (p=0.000).